Proceedings of the symposium on manpower issues in key sectors of the Malaysian economy, February 26, 2013, Putrajaya, Malaysia - Symposium on Manpower Issues in Key Sectors of the Malaysian Economy (2013 : Putrajaya, Malaysia); Maimunah Aminuddin; Malaysia. Kementerian Sumber Manusia; Institut Maklumat dan Analisis Pasaran Buruh; The World Bank (Selangor : ILMIA, 2013)
PSZJBL